Diseño de un sistema administrativo, financiero y contable para la empresa Assis-Prev S.A. del cantón Quito - Medina Vargas, Jenny Elizabeth (2014)
ASSIS - PREV S.A., is a company dedicated to provide funeral services that focus on supporting families in difficult times, with the purpose of becoming a new establishment in the Ecuadorian market that focuses on the lack of processes, regulations and policies that are a problem in this society, but are indispensable in the business cycle of the company to maintain specific control and to prevent adverse involvement from activities to objectives, we plan on correcting this by implementing an Administrative, Financial and Accounting System guide to cover needs for business management. The Administrative, Financial and Accounting System is created for the need to develop alternatives that are able to cover deficiencies in the internal and external procedures of the company, with the main purpose of interacting individual departments based on the mission, vision and objectives. And through the development of strategies, values and principles manuals will be made, in order to meet the special characteristics in terms of organization, structure and responsibilities of the various areas of work.